PENGARUH KELEMAHAN SISTEM PENGENDALIAN INTERNAL, KETIDAKPATUHAN PADA PERATURAN PERUNDANG-UNDANGAN DAN PENYELESAIAN KERUGIAN NEGARA TERHADAP OPINI BPK-RI ATAS LAPORAN KEUANGAN PEMERINTAH DAERAH DI INDONESIA - Maabuat, Justisia Sulastri; Morasa, Jenny; Saerang, David P. E. (ACCOUNTABILITY, 2016)
This study aimed to examine the effect of the internal controls weaknesses, non-compliance with the laws and regulations and the settlement of regional losses against  granting BPK-RI audit opinion on LKPD in Indonesia. The sample in this study amounted to  230 LKPD 2014 throughout Indonesia and used multinominal logistic regression analysis. This study used secondary data which obtained by the Information and Communication Centre (PIK) BPK-RI. The results showed that the  accounting controls and reporting system weaknesses (KSPAP), theimplementation system of the budget revenue and expenditure weaknesses, the non-compliance with laws and regulations that cause  value of local losses influence the granting BPK-RI audit opinion. The internal control structure weaknesses, adherence to laws and regulations that lead to the potential loss of area, a lack of revenues and irregularities in the administration and the settlement of regional losses do not affect granting BPK-RI audit opinion on LKPD. Keywords: The internal control system weaknesses, non-compliance with the laws and regulations, the settlement of regional losses, BPK-RI audit opinion, LKPD